Prediksi Jumlah Pengunjung Pantai Bolihutuo Mengunakan Metode Fuzzy Time Series - Hasan, Maryam (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2023)
Abstract - This research is to find out the results of applying the Fuzzy time series method in predicting the number of visitors to Bolihutuo tourism each month which experiences ups and downs, this condition results in unpreparedness from the officers and administration of Bolihutuo tourism. Bolihutuo visitor data was taken from daily data from January 3 2021 to February 23 and then processed by making predictions using the fuzzy time series method. From the results of the processing carried out, we obtained a fairly good level of prediction accuracy with an accuracy value of 98.96242716% and a Mean Absolute Percentage Error (MAPE) value of 1.037572843%. From the accuracy results obtained and also the mean Absolute Percentage Error (MAPE) value obtained, it can be concluded that the prediction system obtained good results. Keywords: visitors, Bolihutuo beach, tourism, prediction, Fuzzy Time